A new 3D center of mass control approach for FES-assisted standing: First experimental evaluation with a humanoid robot. Issue 11 (November 2016) - Jovic, J.; Bonnet, V.; Fattal, C.; Fraisse, P.; Azevedo Coste, Ch.
Highlights: Restoring the coordination between upper (functional) and lower (paralyzed) limbs in the context of Functional Electrical Stimulation (FES) assisted posture and transfer in complete paraplegic individuals. New automatic control framework. Original paradigm consisting in a kinematic decoupling between lower and upper limbs. Controlling the 3D whole body center of mass location by acting only on the lower limb joints. Validation of the paradigm is performed using a humanoid robot. Abstract: This paper proposes a new control framework to restore the coordination between upper (functional) and lower (paralyzed) limbs in the context of functional electrical stimulation in completely paraplegic individuals. A kinematic decoupling between the lower and upper limbs controls the 3D whole-body center of mass location and the relative foot positions by acting only on the lower-limb joints. The upper limbs are free to move under voluntary control, and are seen as a perturbation for the lower limbs. An experimental validation of this paradigm using a humanoid robot demonstrates the real-time applicability and robustness of the method. Different scenarios mimicking the motion of a healthy subject are investigated. The proposed method can maintain bipedal balance and track the desired center of mass trajectories under movement disturbances of the upper limbs with an error inferior to 0.01 m under any conditions.